2020
DOI: 10.4097/kja.19272
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for the patient with a recently diagnosed concussion: think about the brain!

Abstract: Some patients require emergent, urgent, or elective surgery in the time period immediately following diagnosis of concussion. However, changes in brain homeostatic mechanisms following a concussion and concern for secondary brain injury can complicate the decision as to whether or not a surgery should proceed or be postponed. Given the paucity of available evidence, further evaluation of the use of anesthesia in a patient with concussion is warranted. This article summarizes what is currently known about the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…A retrospective cohort study reported that early orthopedic and facial fracture fixation (≤ 24 h after injury) under general anesthesia was not associated with worse neuropsychological or functional outcome than late surgery in multisystem trauma patients with TBI [ 83 ]. Currently, there are no contraindications to anesthesia in TBI, and once the decision to proceed with surgery has been made, steps should be taken to reduce the risks associated with surgery based on an understanding of the pathophysiology of TBI and the interactions between surgery and application of anesthesia [ 84 ].…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…A retrospective cohort study reported that early orthopedic and facial fracture fixation (≤ 24 h after injury) under general anesthesia was not associated with worse neuropsychological or functional outcome than late surgery in multisystem trauma patients with TBI [ 83 ]. Currently, there are no contraindications to anesthesia in TBI, and once the decision to proceed with surgery has been made, steps should be taken to reduce the risks associated with surgery based on an understanding of the pathophysiology of TBI and the interactions between surgery and application of anesthesia [ 84 ].…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…Los agentes intravenosos generalmente mantienen el acoplamiento entre CMRO 2 y FSC. Por ello, en la medida que mantenga la PAM, cualquier agente intravenoso puede ser usado en esta población [16], [17]. Usualmente se usa la combinación propofol y remifentanilo (u otro opioide de acuerdo con la expectativa del despertar al final de la cirugía).…”
Section: Mantención De La Anestesiaunclassified
“…De las alteraciones con mayor impacto en el manejo y metas anestésicas se encuentran la disfunción del sistema nervioso autónomo que suele ser importante dentro de las 72 h posterior al trauma y la alteración del FSC que puede durar más de un mes, incluso en TEC leve [16].…”
Section: Cirugía Extracraneal En El Paciente Con Tecunclassified